Technological diversification and the growth of regions in the short and long run - Silvia Rocchetta; Martina Iori; Andrea Mina; Robert Gillanders (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
We study the effects of different types of technological diversification on the performance of regional economies. We focus on the relatedness and unconventionality of technological capabilities as drivers of GDP and employment growth. Using economic indicators from Eurostat regional statistics and patent records from the European Patent Office (EPO) PATSTAT and the OECD RegPat databases, we estimate Panel Vector Autoregression models and generate Impulse Response Functions to assess to what extent and with what persistence relatedness and unconventionality affect growth. Our findings, which have implications for place-based innovation policies, reveal that technological relatedness has short-term effects on employment growth and negative effects on GDP growth, whereas technological unconventionality has a long-lasting positive impact on GDP growth and no effect on employment growth.
Keywords: O33; R11; 330; Technological capabilities; Diversification; Relatedness; Unconventionality; Innovation; Regional development